2014
DOI: 10.3109/09637486.2014.918590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of micronized starfruit (Averrhoa carambolaL.) fiber concentrate on lipid metabolism in mice

Abstract: The objective of this study was to evaluate the effect of micronized insoluble fiber from starfruit bagasse as an ingredient of a functional food (FF) or as micronized insoluble fiber-rich fraction (IFRF) and its effects in vivo on lipids metabolism in a murine model. Experimental animals were divided in four isoproteic (15.8%) treatments differing on the fiber and cholesterol level used. The micronized IFRF particle size ranged from 37.5 to 149 μm. Treatments with added IFRF and those including the FF lowered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…As there are almost no previous data on the effects of cereal fibre on NAFLD in humans or animals, we can only speculate about an underlying possible, plausible explanation. Rodent trials on fibre and NAFLD reported concomitant improvements in serum triglyceride and cholesterol levels, which we did not see [46,47,48]. Given the heterogeneous nature of T2DM and its “precursor”, prediabetes, certain subphenotypes might benefit from cereal fibre in a more extensive manner than others.…”
Section: Discussionmentioning
confidence: 62%
“…As there are almost no previous data on the effects of cereal fibre on NAFLD in humans or animals, we can only speculate about an underlying possible, plausible explanation. Rodent trials on fibre and NAFLD reported concomitant improvements in serum triglyceride and cholesterol levels, which we did not see [46,47,48]. Given the heterogeneous nature of T2DM and its “precursor”, prediabetes, certain subphenotypes might benefit from cereal fibre in a more extensive manner than others.…”
Section: Discussionmentioning
confidence: 62%
“…A study done in 2014 by Herman‐Lara et al found that feeding of micronized star fruit fiber concentrate to C57BL/6 mice significantly lowers the concentrations of serum triacylglycerides, serum total cholesterol, and liver lipids to different extents. It did this by enhancing the excretion of lipids and cholesterol (Herman‐Lara et al., 2014). Wu et al found microsized star fruit fibers lower the concentrations of serum triglyceride (by 15.6%–17.8%) and serum total cholesterol (by 15.7%–17.0%).…”
Section: Results and Discussion Of Trendsmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are among the most common causes of death globally, with hyperlipidemia representing one of its main risk factors ( Mahdavi et al, 2020 ; Jayachandran and Qu, 2021 ). In Herman-Lara et al (2014) evaluation of the protective activity of micronized insoluble fiber from the bagasse of A. carambola as an ingredient of a functional food (FF) or as micronized insoluble fiber-rich fraction (IFRF) and its effects in vivo on lipid metabolism in a murine model, serum TG, TC, HDL-C, and LDL-C decreased after a murine model was treated with IFRF and FF, with corresponding inhibition rates of 14.2, 25.4, 55.06, and 12.18% by IFRF, and 30.18, 39.47, 35.11, and 43.18% by FF. IFRF treatment also produced higher hypolipidemic activity and greatly avoided the occurrence of non-alcoholic fatty liver.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…IFRF treatment also produced higher hypolipidemic activity and greatly avoided the occurrence of non-alcoholic fatty liver. Overall, IFRF and FF exerted hypolipidemic qualities, indicating that the star fruit’s insoluble fiber is potentially a component of FFs in the treatment and prevention of CVDs ( Herman-Lara et al, 2014 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%